Efeito do alumínio sobre a fotossíntese em dois cultivares de sorgo - Cambraia, José; Pires de Lemos Filho, José; Oliva, Marco Antônio; de Moura Estevão, Márcio (Revista Ceres, 2025)
The effects of aluminum (0, 2, 4, 6 and 8 ppm) on photosynthesis rate, chlorophyll content, dry weight and activity of some oxidases were studied in two cultivars of sorghum, one Al-tolerant (CMS X S — 106) and one Al — sensitive (CMS X 8 —903).